2018
DOI: 10.15414/jmbfs.2018.7.4.432-436
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Micro and Trace Elements of Commercial Beers

Abstract: In the present paper, a risk analysis of beer’s element content has been carried out. Al, As, Ba, Cd, Co, Cr, Cu, Fe, Mo, Mn, Ni, Se, Sr, Pb and Zn were determined by Inductively Coupled Plasma Mass Spectrometry (ICP-MS) in 24 beer samples produced by different breweries. Samples could be originated from Hungary, Belgium, the Czech Republic, Germany and Austria, and the set consisted of 4 types of beer: pale barley, dark barley, pale wheat and dark wheat samples. It appeared that Mn was the most abundant among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…In the tested beer-based low percentage aromatic alcoholic beverage samples, elements such as Cd, Co, Cr, Cu, Fe, Mn, Pb, Sr and Zn showed relatively high compliance with the works of other researchers [ 13 , 28 ]. The levels of Ba, Ni and Al determined in this study were higher than those found in the literature, and in some cases, even the standards available for drinking water provided by WHO were exceeded.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…In the tested beer-based low percentage aromatic alcoholic beverage samples, elements such as Cd, Co, Cr, Cu, Fe, Mn, Pb, Sr and Zn showed relatively high compliance with the works of other researchers [ 13 , 28 ]. The levels of Ba, Ni and Al determined in this study were higher than those found in the literature, and in some cases, even the standards available for drinking water provided by WHO were exceeded.…”
Section: Resultssupporting
confidence: 67%
“…Table 5 compares the ranges of results obtained in this study with the results of other researchers, where elemental analysis was also carried out for ciders [ 6 , 19 ] and beers [ 13 , 26 ]. In the case of the results for ciders, for most of the determined elements (Al, B, Ba, Bi, Cd, Cr, Ca, K, Mg, Na, Li, Mn, Ni, Pb, Ti, Tl and Zn), full compliance was obtained with ranges given by García-Ruiz et al (2007) [ 19 ] and Cristea et al (2019) [ 6 ].…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…However, it has little influence on the taste of the beer (Pohl, 2008). The magnesium content was lower than the mean value of 126 mg/L obtained by Alexa et al (2018), as were the potassium levels (412.5 mg/L) in the ginger craft beer produced by Martínez et al (2017). High concentrations of magnesium contribute to the bitterness of beer, and its recommended concentration can be up to 30 mg/L (Pohl, 2008).…”
Section: Centesimal and Mineral Compositionmentioning
confidence: 79%
“…Other alcoholic beverages which have been studied by means of multi-element distribution are whiskey [ 67 , 68 , 69 ], cider [ 70 , 71 ], beer [ 72 , 73 , 74 , 75 ] and Chinese liquors [ 76 ]. Gajek and co-workers [ 69 ] studied extensively diverse varieties and ages of whiskey from different geographical regions and production procedures.…”
Section: Discussionmentioning
confidence: 99%